2015
DOI: 10.1016/j.athoracsur.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Assessment and Impact on Survival in Video-Assisted Thoracoscopic Lobectomy or Segmentectomy

Abstract: Sampling greater than 3 LNS and greater than 10 RNs was associated with an increase in nodal upstaging. Only LNS greater than 3 was found to be an independent predictor of mortality in VATS lobectomy and segmentectomy in clinical early-stage NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
1
22
2
Order By: Relevance
“…Patients having had less than 11 LNs dissected had significantly less recurrentfree survival, but no effect on overall mortality. Previous studies have shown different results, with number of LNs dissected affecting both overall survival and lung overall survival (2,6,7,12). Possible reasons for the discrepancy could be the small sample size of this present study which carries less statistical power, the shorter follow-up time, or different techniques of data analysis.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Patients having had less than 11 LNs dissected had significantly less recurrentfree survival, but no effect on overall mortality. Previous studies have shown different results, with number of LNs dissected affecting both overall survival and lung overall survival (2,6,7,12). Possible reasons for the discrepancy could be the small sample size of this present study which carries less statistical power, the shorter follow-up time, or different techniques of data analysis.…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have shown that systematic LN dissection (SLND) could improve staging (2)(3)(4)(5) and overall survival compared to LN sampling (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The reason why more LN scope resulted in a better prognosis might be more accurate staging and less false-negative stage I NSCLC patients (13). Zhou reported that more than 3 LN stations or 10 resected LN were associated with an increase in nodal upstaging and more exact staging (32). Moreover, sampling more than 3 LN stations was found to be an independent predictor for long-term outcomes of lobectomy and segmentectomy in clinical early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited resections like wedges and segmentectomies have recently been reconsidered (32)(33)(34), particularly in the elderly and high-risk population. The previously well documented overall survival benefits of lobectomy over limited resections are not observed in patients older than 75 years (25,(35)(36)(37).…”
Section: General Considerationsmentioning
confidence: 99%